The Grieving Status of the Primary Schoolchildren as the Factor of their Socialization - Butvilas, Tomas (Acta Paedagogica Vilnensia, 2006)
Within this paper the primary school grieving children's status in the classroom is discussed, and revealed. It is important to stress that the experienced losses in the family for those students are mainly divorce, parents' unemployment, and death of the parent or grandparent. On the basis of empirical data the children's status and their view to it are compared. Scilicet children's view into their status and the real status' fact in the classroom are main factors for those students' (especially the grieving ones) socialization: it was stated that there are more grieving children with lower status in the classroom than those who have not experienced any loss in the family (p < 0,002). Although it depends on what kind of activity was chosen to do with these students, e.g. Children, who have experienced loss in the family, sometimes have a higher status than their classmates, because of their compassion, openness etc. The differences between genders were found as well, i.e. both grieving and non-grieving boys have shown their lower status than the girls of the same age. The other important reveal in this research is this, that most of the children have had pointed their positive view to the status in the classroom and feel comfortable about it. However, children who have experienced parents' unemployment, divorce, and the death of a loved one, receive their status more negative than the others, and also feel uncomfortable about it. All that shows that experienced losses in the family in some ways have much negative influence for those students' status, and, as the consequence of this, it obviously refers to the negative view to the status. As the matter of fact, it aggravates such children's socialization in regard to value internalization, and self-identification with whom.
Keywords: primary school; grieving children; socialization; status